Predictors of Pneumonitis in Patients With Locally Advanced Non-Small Cell Lung Cancer Treated With Definitive Chemoradiation Followed by Consolidative Durvalumab - Brett H. Diamond, MD; Neel Belani, MD; Rebecca Masel, MD; Kathryn DeCarli, MD, MBE; Thomas DiPetrillo, MD; Jaroslaw T. Hepel, MD; Christopher G. Azzoli, MD; Humera Khurshid, MD; Abbas Abbas, MD; Paul P. Koffer, MD (Advances in Radiation Oncology, 2023)
Purpose: In patients with locally advanced, unresectable non-small cell lung cancer (NSCLC), the standard of care is concurrent chemoradiation (CRT) followed by consolidative immunotherapy with durvalumab. Pneumonitis is a known adverse event of both radiation therapy and immune checkpoint inhibitors such as durvalumab. We sought to characterize pneumonitis rates and dosimetric predictors of pneumonitis in a real-world population of patients with NSCLC treated with definitive CRT followed by consolidative durvalumab. Methods and Materials: Patients with NSCLC from a single institution who were treated with definitive CRT followed by consolidative durvalumab were identified. Outcomes of interest included pneumonitis incidence, type of pneumonitis, progression-free survival, and overall survival. Results: Sixty-two patients were included in our data set treated from 2018 to 2021 with a median follow-up of 17 months. The rate of grade 2+ pneumonitis in our cohort was 32.3%, and the rate of grade 3+ pneumonitis was 9.7%. Lung dosimetry parameters including V20 ≥30% and mean lung dose (MLD) >18 Gy were found to be correlated with increased rates of grade 2+ and grade 3+ pneumonitis. Patients with a lung V20 ≥30% had a grade 2+ pneumonitis rate at 1 year of 49.8% compared with 17.8% in patients with a lung V20 <30% (P = .015). Similarly, patients with an MLD >18 Gy had a grade 2+ pneumonitis rate at 1 year of 52.4% compared with 25.8% in patients with an MLD ≤18 Gy (P = .01). Moreover, heart dosimetry parameters including mean heart dose ≥10 Gy were found to be correlated with increased rates of grade 2+ pneumonitis. The estimated 1-year overall survival and progression-free survival of our cohort were 86.8% and 64.1%, respectively. Conclusions: The modern management of locally advanced, unresectable NSCLC involves definitive chemoradiation followed by consolidative durvalumab. Pneumonitis rates were higher than expected in this cohort, particularly for patients with a lung V20 ≥30%, MLD >18 Gy, and mean heart dose ≥10 Gy, suggesting that more stringent radiation planning dose constraints may be needed.